"Sleeper" Antiquities: Misattributions in Sales of Ancient Art. Issue 1 (February 2020) - Marrone, James; Beltrametti, Silvia
Abstract: "Sleepers" are artworks or collectibles that are undervalued because one or more characteristics go unrecognized. This article discusses 12 sleepers that have been sold at auction on the antiquity market since 2007 whose attribution as antiquities were originally overlooked, either accidentally or deliberately. The objects are presented in the context of a theoretical framework describing both the legal and economic incentives to perform due diligence and to reveal, or "awaken, " a sleeper antiquity. The theory implies that sleepers may arise for several reasons, and the case studies are grouped accordingly. Most pressingly, the analysis identifies two ways in which sellers are disincentivized to be transparent about an object's identity: when they can exploit legal loopholes to deliberately misattribute an antiquity and mediate export and when they can hide disagreement about an object's authenticity to mediate its sale. Placing the case studies in the broader market context, we highlight particular areas that should be addressed by policy or regulatory reform. The analysis also has wider applications to other forms of art.